HUBUNGAN KECEMASAN IBU MENYUSUI DENGAN KELANCARAN PENGELUARAN AIR SUSU IBU (ASI ) DI BPS KERTA TIMUR KECAMATAN DASUK KABUPATEN SUMENEP: Relationship Between Mother's Anxiety Analysis With The swiftness of Breast Milk In BPS Kerta Timur Kecamatan Dasuk Kabupaten Sumenep - Sri Yunita Suraida Salat; Emdat Suprayitno (LPPM - STIKES Pemkab Jombang, 2019)
ABSTRACT Preliminary; Nowdays, We can meet some breastfeeding mother who doesnt”t give her breast milk for her baby. It related with the preliminary study in the Kerta Timur village, Dasuk Subdistrict, Sumenep District, it is known that breastfeeding mothers who have visited during childbirth complained that they could not give their breast milk because their breast milk did not come out at all. Purpose; Analyze the Relationship of Breastfeeding mother Anxiety Mothers with the swiftness of Breast Milk (ASI). Method; This research is included as analytic research which using correlation analytic. Design In this study using the HARS Questionnaire and checklist which analyzed using the Spearman Test with 0.05 significance level. Results; Based on the Spearman correlation test, the value of ?-value = 0,000 means that there is a relation between the anxiety of breastfeeding mothers and the swiftness of breastfeeding in BPS Kerta Timur, Dasuk District, Sumenep Regency. Conclusion; Most of breastfeeding mothers fell anxiety and more than half of breastfeeding mothers get non-expending in breast milk. There is a relationship between breastfeeding mothers anxiety with the swiftness of breast milk.